Towards an Accountable Capitalism - Davis, Stephen; Lukomnik, Jon; Pitt-Watson, David (World Bank, Washington, DC, 2012)
The global credit crisis has been a systemic failure. In this monograph, the author try to set out some of what went wrong, and how to develop the framework of policy and institutions needed to ensure a vibrant and stable financial system in the future. This will require new thinking about the type of institutions on which a successful modern financial economy depends, but, more importantly, on the relationship between each of these institutions. The author focuses on how to get them to work in a way which will support open and effective capital markets. The aim is not to lay out a detailed framework for bank solvency, or accounting regulation or corporate governance, though the author will touch on many examples of reform. Rather it is to try to clarify the principles on which any responsible market system will rest, and how these might be applied to the banks and the other markets where finance is raised to keep the economy going. It is also to suggest various actions the participants in all markets - regulators, investors, Non-governmental Organizations (NGOs), and bankers, can take to prevent similar disasters.